Site mapping and small molecule blind docking reveal a possible target site on the SARS-CoV-2 main protease dimer interface. (December 2020) - Liang, Julia; Karagiannis, Chris; Pitsillou, Eleni; Darmawan, Kevion K.; Ng, Ken; Hung, Andrew; Karagiannis, Tom C.
Graphical abstract: Highlights: The SARS-CoV-2 main protease (M pro ) has an important role in the viral life cycle. Inhibition of the active site or dimerization site of M pro can mitigate activity. Mapping reveals a reactive pocket in the dimerization pocket at the apex of M pro . Blind docking shows that ligands may preferentially bind at the apex of M pro . Stable ligand interactions are formed at the active and apex sites of M pro . Abstract: The SARS-CoV-2 virus is causing COVID-19 resulting in an ongoing pandemic with serious health, social, and economic implications. Much research is focused in repurposing or identifying new small molecules which may interact with viral or host-cell molecular targets. An important SARS-CoV-2 target is the main protease (M pro ), and the peptidomimetic α-ketoamides represent prototypical experimental inhibitors. The protease is characterised by the dimerization of two monomers each which contains the catalytic dyad defined by Cys 145 and His 41 residues (active site). Dimerization yields the functional homodimer. Here, our aim was to investigate small molecules, including lopinavir and ritonavir, α-ketoamide 13b, and ebselen, for their ability to interact with the M pro . The sirtuin 1 agonist SRT1720 was also used in our analyses. Blind docking to each monomer individually indicated preferential binding of the ligands in the active site. Site-mapping of the dimeric protease indicated a highly reactive pocket in the dimerization region at the domain III apex. Blind docking consistently indicated a strong preference of ligand binding in domain III, away from the active site. Molecular dynamics simulations indicated that ligands docked both to the active site and in the dimerization region at the apex, formed relatively stable interactions. Overall, our findings do not obviate the superior potency with respect to inhibition of protease activity of covalently-linked inhibitors such as α-ketoamide 13b in the M pro active site. Nevertheless, along with those from others, our findings highlight the importance of further characterisation of the M pro active site and any potential allosteric sites.